Organic Waste Management in Hotels in the Province of Lima (Peru). Logistical proposals from a circular economy perspective - Munguía-Guillen, Kiara; Rojas-Campos, Valerie; Ruiz-Ruiz, Marcos Fernando; Quiroz-Flores, Juan Carlos; Albarracin-Manrique, Marcos Antonio (LACCEI, 2025)
The objective of this research was to design and validate logistic proposals under a circular economy approach, oriented to optimize the management of organic waste in hotels in the province of Lima. A non-experimental, descriptive and applied design methodology was applied, using industrial engineering tools and structural modeling techniques. Through structural equation analysis (SEM), critical operational variables were identified, such as personnel training, supervision and separation infrastructure, and the significant influence of managerial and municipal actors in decision making was determined. In response to these findings, the application of Failure Mode and Effects Analysis (FMEA) was proposed as a technical mechanism to intervene in critical points in the hotels' internal logistics process. This solution was evaluated for its technical relevance, replicability, and alignment with current regulations. It is concluded that the developed model represents a viable alternative to promote organic valorization from an operational and sustainable perspective in Latin American urban contexts.